Pemanfaatan Artificial Intelligence dalam Pembelajaran Matematika untuk Siswa di SMP Insan Rabbany - Jan Setiawan; Noni Dwi Sari; Yuniar Istiyawati (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Since the introduction of ChatGPT as artificial intelligence and its massive development over the years, it has had a huge impact on various aspects of life, and it is increasingly visible in the presence of increasingly advanced features, functions, and appearances. Its use in the field of education has not escaped the advancement of artificial intelligence. For some teachers and students, the term artificial intelligence is still very new, as is its use in the teaching and learning process. Currently, Indonesia's use of artificial intelligence faces numerous unavoidable obstacles and challenges. However, in global education, it is becoming increasingly common to use artificial intelligence in the teaching and learning process. The introduction of artificial intelligence to junior high school students is considered very appropriate because students' psychology at this level is more developed, and the learning load begins to increase compared to the elementary level. Math subjects for most students are still a scourge. In this community service, artificial intelligence is introduced to students of the exchange program class at SMP Insan Rabbany, which is related to mathematics learning, so that it can help in student learning. The results of the community service evaluation showed high student enthusiasm regarding the use of artificial intelligence, both to aid learning and for other purposes.